La gioconda an opera in four acts the libretto by Tobia Gorrio Vocal score arranged by Michele Saladino - PONCHIELLI, A. (G. Ricordi & Co)
Opening chorusnscene & trionrecit, regatta chorusnromanzanscene & duettnetc.